2013
DOI: 10.1002/cbic.201300153
|View full text |Cite
|
Sign up to set email alerts
|

A Single PLP‐Dependent Enzyme PctV Catalyzes the Transformation of 3‐Dehydroshikimate into 3‐Aminobenzoate in the Biosynthesis of Pactamycin

Abstract: Natural amino donation: A PLP-dependent aminotransferase PctV, encoded in the pactamycin biosynthetic gene cluster, was found to catalyze the formation of 3-aminobenzoate from 3-dehydroshikimate with L-glutamate as the amino donor. The PctV reaction comprises a transamination and two dehydration reactions. This is the first report of a simple 3-ABA synthase in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Recently, a 3AB biosynthetic pathway was identified, which employs an aminotransferase/3AB synthase to convert 3‐dehydroshikimic acid (DHS) to 3AB using L‐glutamic acid as the amino donor . Notably, DHS is a key intermediate of the shikimate pathway that is ubiquitously used by bacteria, algae, fungi and plants for making aromatic amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a 3AB biosynthetic pathway was identified, which employs an aminotransferase/3AB synthase to convert 3‐dehydroshikimic acid (DHS) to 3AB using L‐glutamic acid as the amino donor . Notably, DHS is a key intermediate of the shikimate pathway that is ubiquitously used by bacteria, algae, fungi and plants for making aromatic amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…34−39 BtrR, a dual functional aminotransferase for the biosynthesis of 2-DOS in butirosin, has also been biochemically and structurally characterized. 40,41 Surprisingly, limited examples were available on the biochemical and structural characterization of aminotransferases responsible for scaffold construction/modification in the biosynthesis of bacterial secondary metabolites, including OxyQ (anhydrotetracycline, in vivo studies), 42 Neo-18 (neomycin) and BtrB (butirosin), 43 PvdH (pyoverdinesiderophore), 44 YwfG (anticapsin), 45 PctV (pactamycin), 46,47 and GenS2 (gentamycin). 48 The crystal structure of PigE, 49 an aminotransferase in prodigiosin biosynthesis, 50 was recently reported.…”
mentioning
confidence: 99%
“…Further, PctL (PtmJ) was characterized as a glycosyltransferase that catalyzes transglycosylation between UDP‐ N ‐acetyl‐ d ‐glucosamine (UDP‐GlcNAc) and 3AAP to produce N ‐acetyl‐ d ‐glucosaminyl‐3‐aminoacetophenone (GlcNAc‐3AAP, 2 ) . However, 3AAP was not incorporated into pactamycin; this indicated that the physiological substrate of PctL was 3ABA or its thioester derivatives such as 3‐aminophenyl‐β‐oxopropanoic acid thioester, which would undergo hydrolysis and decarboxylation to give the 3AAP moiety . Mahmud and co‐workers reported that a mutant with a knockout of a discrete acyl carrier protein PtmL (PctK) did not accumulate any pactamycin biosynthetic intermediates .…”
Section: Methodsmentioning
confidence: 99%